The Effect of Screw-in Studs on Equine Hoof and Limb Kinematics while Cantering and Jumping on an Artificial Surface - Thomas Dunbar; Soraya Morscher (International Journal of Equine Science)
Studs are used to optimize hoof grip upon contact with the surface to prevent slip and enhance performance. Previous research has explored the influence of uniaxially placed studs on a grass surface during canter, the influence of stud length on braking forces, and the effect of restricted foot slip on bone strains. However, previous work has not addressed the influence of biaxially placed screw-in studs during canter and jumping on an artificial surface. A study was designed using seven actively competing showjumping horses which were subjected to two treatments: no studs (control) and studs. Studs were placed biaxially in the heel of each shoe. Kinematic analysis was conducted using high-speed video footage during canter and jumping. The test fence was set at a height of 1.20m with a width of 1m. No differences in slip distance or slip duration were observed across all phases (P > 0.05). A decrease in stance duration of the leading forelimb was seen at jump landing (P < 0.05). Take-off angle increased by 4.5° (P < 0.05), elbow angle during suspension was more acute (P < 0.05) and landing distance from the fence was greater by 0.31m (P < 0.05). The study demonstrates that canter kinematics were largely unaffected by stud use on an artificial surface; however, unexpectedly, some jumping parameters significantly improved. A reduction in the stance duration at jump landing is concerning as this may lead to higher braking forces in the distal limb, potentially resulting in an increased risk of overload injuries.